Analisis Tindak Tutur Ilokusi pada Teks Negosiasi dalam Buku Bahasa Indonesia Edisi Revisi (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2026)
In conveying messages, speakers use utterances. Utterances are forms of speech that contain various communicative functions according to the context and purpose of communication. Speech acts are the main element in verbal interactions that reflect social actions in the form of speech. Speech acts are actions manifested in the form of speech that have a special meaning. One type of speech act is the illocutionary speech act. The purpose of this study is to analyze and describe the types and forms of illocutionary speech acts in negotiation texts in the revised edition of Indonesian language books. This research method uses qualitative descriptions and pragmatic analysis. Data collection in this study uses reading and note-taking techniques and purposive sampling. Based on the data analysis, the author has identified 171 illocutionary speech acts, including assertive, directive, commissive, expressive, and declarative. Based on the research, the author found that assertive, directive, and expressive speech acts predominate. Commissive speech acts numbered twenty-seven, and declarative speech acts numbered the least, namely seven. This research is expected to provide students with an understanding of the types of illocutionary speech acts, enhance their knowledge, and enable them to use them effectively and correctly.